2019
DOI: 10.1371/journal.pone.0225307
|View full text |Cite
|
Sign up to set email alerts
|

Risk of temperature, humidity and concentrations of air pollutants on the hospitalization of AECOPD

Abstract: AimTo investigate the effect of temperature, humidity and the concentration of ambient air pollution on the hospitalization of AECOPD.MethodHospitalization record was obtained from Shenyang Medical Insurance Bureau, concluding patient’s age, gender, income hospital time, outcome hospital; Generalized additive model was used to analyze the relationship between temperature, humidity, the concentration of ambient air pollution and the hospitalization of AECOPD.ResultThe effect of ozone on admission rate in male g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…We used the distributed delayed non-linear model (DLNM) to determine the association between ambient temperature and disease. The DLNM can be used as an index of the relationship between cumulative hysteresis effect, exposure, and response as shown in equation ( 1 ) (Gasparrini et al 2010 ; Forbes 2010 ): where α is the intercept value; φ 1 , φ 2 , and φ 3 are regression correlations; E [(yt)] is the expected number of daily admissions at day t ; df is the degrees of freedom; Temperature is ambient temperature; humidity is the daily relative humidity; pressure is the daily average pressure; dow is a dummy variable for the day of the week; ns represents a smoothed function of time (df = 4), pressure (df = 5), and humidity (df = 3) (Chen et al 2019 ; Song et al 2019 ; Luo et al 2018a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the distributed delayed non-linear model (DLNM) to determine the association between ambient temperature and disease. The DLNM can be used as an index of the relationship between cumulative hysteresis effect, exposure, and response as shown in equation ( 1 ) (Gasparrini et al 2010 ; Forbes 2010 ): where α is the intercept value; φ 1 , φ 2 , and φ 3 are regression correlations; E [(yt)] is the expected number of daily admissions at day t ; df is the degrees of freedom; Temperature is ambient temperature; humidity is the daily relative humidity; pressure is the daily average pressure; dow is a dummy variable for the day of the week; ns represents a smoothed function of time (df = 4), pressure (df = 5), and humidity (df = 3) (Chen et al 2019 ; Song et al 2019 ; Luo et al 2018a ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that ambient temperature may be an important risk factor for COPD, stroke, and MI in China (Chen et al 2019 ; Qi et al 2020 ). One study conducted in Changchun, China, that evaluated changes in ambient temperature on consecutive days found that the elderly and females were at a greater risk of acute disease exacerbation (Ma et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One ecologic study conducted in China illustrated that SARS patients from regions with high-level air pollution were twice as likely to die from SARS compared to those from regions with low-level air pollution [11] . Several researches pointed out that air pollution, ambient temperature and relative humidity had an adverse effect on respiratory symptoms [12][13][14] . Wuhan city belongs to the north subtropical monsoon (humid) climate, with abundant perennial rainfall, sufficient heat, rain, and heat in the same season, light and heat in the same season, cold in winter and hot in summer.…”
Section: Introductionmentioning
confidence: 99%
“…One ecologic study conducted in China illustrated that SARS patients from regions with high-level air pollution were twice as likely to die from SARS compared to those from regions with low-level air pollution [11]. Several researches pointed out that ambient temperature and relative humidity had an adverse effect on respiratory symptom [12][13][14].…”
Section: Introductionmentioning
confidence: 99%